Identification and Growth Characteristics of Cellulase Producing Bacteria (Bangladesh Journal of Botany, 2024)
This study was envisaged to from fresh cow dung using the Congo red staining method, and screened by measuring their endoglucanase activity (CMC enzyme activity), exoglucanase activity (Cex enzyme activity), and filter paper enzyme activity (FPA enzyme activity). Subsequently, the molecular, morphological characteristics, and growth characteristics were studied. Three strains showed clear transparent circles on the Congo red cellulose medium. LY3 exhibited strong enzyme production ability, with relatively higher enzyme activity than the other two strains. LY3 was found to be a dominant strain that required a temperature of 40℃and pH 7.0 for optimal growth. Based on the molecular and  morphological characteristics, the three strains were preliminarily identified as Bacillus.Bangladesh J. Bot. 53(3): 849-856, 2024 (September) Special